2022
DOI: 10.1038/s41598-022-17708-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in bull semen quality demonstrates there are heat-sensitive and heat-tolerant bulls

Abstract: Using semen data from 1271 ejaculates (79 different bulls, 11 different breeds) we have investigated the variability of semen quality in cattle living in sub-tropical conditions. Modelling shows definitive evidence of seasonal variation. Semen quality from the same bulls had a 90% “pass rate” for cryopreservation purposes in winter, dropping to less than 50% in summer. Notably, individual bulls could be classified as either “heat-tolerant” (produce good quality spermatozoa all year regardless of temperature) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
(51 reference statements)
4
4
0
Order By: Relevance
“…Some stallions did not present biologically meaningful relationships between climatic conditions, fertility, or DNA damage, whereas others presented consistent, strong relationships. This is in keeping with studies in cattle that have also reported differences in the heat tolerance of individual bulls (Netherton et al, 2022;Vogler et al, 1993;Vogler et al, 1991;Walters et al, 2005). Netherton et al (2022) reported that ambient temperatures greater than 34°C resulted in poor sperm production in 63% of bulls assessed, with the spermatozoa of the remaining 37% unaffected.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some stallions did not present biologically meaningful relationships between climatic conditions, fertility, or DNA damage, whereas others presented consistent, strong relationships. This is in keeping with studies in cattle that have also reported differences in the heat tolerance of individual bulls (Netherton et al, 2022;Vogler et al, 1993;Vogler et al, 1991;Walters et al, 2005). Netherton et al (2022) reported that ambient temperatures greater than 34°C resulted in poor sperm production in 63% of bulls assessed, with the spermatozoa of the remaining 37% unaffected.…”
Section: Discussionsupporting
confidence: 88%
“…Spermatogenesis in the stallions lasts approximately 57 days, followed by a further seven days of epididymal storage (Johnson et al, 1997). Heat related insults, whether via systemic stress or direct, affect germ cells differently depending on their developmental stage at the time of insult (Houston et al, 2018;Netherton et al, 2022). As such, the timing of heat-induced subfertility can inform on the stages of germ cell development most vulnerable to damage (Love and Kenney 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, these same authors did note that bulls found in the hottest part of the country (north region) were less likely to pass a semen test. In support of this, we have reported definitive evidence of seasonal variation within bulls taken from central QLD, Australia [82] where temperatures in summer are exceedingly hot.…”
Section: Is "Heat-stress" Physiologically Relevant?supporting
confidence: 69%
“…We found large changes in semen quality following intervention. Some bulls dropped to below 50% normal forms, whilst others maintained their baseline 80% average throughout 12 weeks of testing [82]. Thus, it is clear that there is a spectrum of thermo-sensitivity within individual animals.…”
Section: Is "Heat-stress" Physiologically Relevant?mentioning
confidence: 98%
“…They have reported on the optimal season for optimal outcomes; nevertheless, contradictory findings have also been published. 8,9 According to the study of Shawki et al, 10 statistical analysis revealed variations in the impact of season on semen parameters. In the tropics, seasonal fluctuations in cattle fertility are common.…”
mentioning
confidence: 99%